2018
DOI: 10.1039/c7ce02121f
|View full text |Cite
|
Sign up to set email alerts
|

Defect-related anisotropic surface micro-structures of nonpolar a-plane GaN epitaxial films

Abstract: The anisotropic surface etching behavior of nonpolar a-plane GaN (112̄0) epitaxial films, grown by pulsed laser deposition, was investigated experimentally by wet chemical etching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The anisotropy in crystalline quality (ACQ) is generally induced by the discrepancy in the in-plane growth rate along different directions. 27,28 In this study, ACQ is defined bywhere FWHM [11̄00] and FWHM [0001] are the XRC FWHM values measured along the [11̄00] and [0001] directions, respectively. FWHM [11̄00] − FWHM [0001] and ACQ as a function of the miscut angle for the two series a -plane GaN film samples are plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anisotropy in crystalline quality (ACQ) is generally induced by the discrepancy in the in-plane growth rate along different directions. 27,28 In this study, ACQ is defined bywhere FWHM [11̄00] and FWHM [0001] are the XRC FWHM values measured along the [11̄00] and [0001] directions, respectively. FWHM [11̄00] − FWHM [0001] and ACQ as a function of the miscut angle for the two series a -plane GaN film samples are plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The anisotropy in crystalline quality (ACQ) is generally induced by the discrepancy in the in-plane growth rate along different directions. 27,28 In this study, ACQ is defined by…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the grain/terrace size distributions and the surface roughness of the non-polar GaN-based photodetector played a huge role in the performance of the device. In addition, it was reported that AFM analysis could be further utilized to confirm the defect densities [31,78]. In other words, the screw dislocation had an impact on the surface, whereby these dislocations could generate a tension tangential to the surface, leading to surface depressions that prevailed the surface [31,79,80].…”
Section: Photoluminescencementioning
confidence: 99%